PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK MELALUI KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2017-2019 - SHINTA EKA PUTRI LUMBANTOBING; HARLYN L SIAGIAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
This study aims to examine the impact of CSR on tax aggressivenes moderated by institutional leadership. The number of samples in this research are 14 14 businesses in the beverage and food sector listed on the IDX for 2017-2019. Using a quantitative approach, secondary data is taken based on reporting every year of sample company were then analyzed using regression analysis method using the SPSS application. in accordance with the ana2lysis carried out in this research, it can be concluded that (1) CSR has negative impact in corporate tax aggressiveness, the better the CSR carried out by the company, the smaller the company’s opportunity to do tax avoidance, (2) Institutional leadership doesnt moderate the influence of CSR on tax aggressiveness. there is a significant difference in the effect of CSR on tax aggressiveness in companies with high institutional leadership and companies in low institutional leadership.